P–460 Impact of various cancers on semen parameters in a tertiary onco-fertility unit in India. (6th August 2021) - Aggarwal, P; Rohatgi, T B; Singh, R; Patel, S; Ghumman, S; Nair, N
Abstract: Study question: This study evaluated differences in semen parameters in male cancer patients in our ethnic population who banked their sperms prior to cancer treatment Summary answer: We found significant differences in semen concentration, motility and morphology between different types of cancers, especially testicular cancers What is known already: Impaired spermatogenesis and abnormal semen parameters in cancer patients has been noted, however certain cancer types are more damaging than others. In testicular cancer, spermatogenesis impairment is more quantitative than qualitative with sperm morphology being the most affected parameter. Among non testicular cancers, lymphoma cases usually show the most significantly impaired semen parameters Study design, size, duration: We conducted a retrospective study analyzing semen parameters in 49 cancer patients between October 2014 to January 2020 who presented to the onco-fertility unit, Max Multispeciality Hospitals, New Delhi. Furthermore, we did our analysis based on total of 101 samples and were broadly divided into testicular (37 samples) and non testicular cancers (64 samples). Patients who had previously received any form of cancer treatment including chemotherapy or radiotherapy were not included in this study Participants/materials, setting, methods: Testicular Cancer(TC) group was further subcategorized into Seminoma and Non Seminoma groups whereas Non Testicular Cancer (NTC) group was subcategorized into Lymphoma and Non Lymphoma groups. Semen was collected by masturbation and analysis was performed in keeping with the WHO criteria. Statistical analyses was performed using SPSS software. p values <0.05 were considered to indicate statistical significance. Main results and the role of chance: In Testicular cancer (TC), 92% samples (34/37) had abnormal semen parameters whereas only 24.4% samples (22/64) were abnormal in Non Testicular cancer (NTC). Additionally, there were significant differences in sperm concentration, motility and morphology between TC and NTC groups. Individually, TC: Oligozoospermia was seen in 73% (27/37) with subdivision between Seminoma and Non Seminoma groups being 81.3% (13/16) and 61.9% (13/21). Asthenozoospermia was seen in 86.5% (32/37) samples with subdivision between Seminoma and Non Seminoma groups being 87.5% (14/16) and 81% (17/21). Teratozoospermia was seen in 59.5% (22/37) samples with subdivision between Seminoma and Non Seminoma groups being 75% (12/16) and 42.86% (9/21). Combined OATS observed in 59.5% (22/37) samples with subdivision between Seminoma and Non Seminoma groups being 75% (12/16) and 42.86% (9/21) NTC: Oligozoospermia was seen in 18.8% (12/64) samples with subdivision between Lymphoma and Non Lymphoma groups being 26.92% (7/26) and 26.32% (10/38). Asthenozoospermia was seen in 32.8% (21/64) samples with subdivision between Lymphoma and Non Lymphoma groups being 34.62% (9/26) and 34.21% (13/38). Teratozoospermia was seen in 17.2% (11/64) samples with subdivision between Lymphoma and Non Lymphoma groups being 26.9% (7/26) and 23.68% (9/38). Combined OATS observed in 17.2% (11/64) samples with subdivision between Lymphoma and Non Lymphoma groups being 26.9% (7/26) and 23.68% (9/38). Limitations, reasons for caution: Study was conducted in a single institution with lesser overall number of patients. Duration, staging and grading of cancers were also not individually assessed, which could be a further limiting factor. Wider implications of the findings: Testicular cancers, especially seminomas, have the most severe effect upon semen parameters. Among NTC patients, lymphomas have the worst impact. Knowing the varying effect of different cancers on semen parameters in our ethnic population helps ART specialists and oncologists to appropriately modify patient counseling and improve fertility outcomes. Trial registration number: RMO13019